2006
DOI: 10.1111/j.1939-1676.2006.tb02840.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Clinical Evolution of Scrapie in Sheep by 3rd Eyelid Biopsy

Abstract: The goal of this article was to characterize the clinical evolution of scrapie in naturally affected sheep. Eighteen sheep with scrapie diagnosed by examination of 3rd eyelid biopsy and 12 control ewes were studied throughout the duration of their disease. Diagnosis was confirmed postmortem by histopathologic, immunohistochemical, and Western blot analysis of nervous tissue. Complete clinical examinations were performed every 2 weeks for each animal, of which 3 clinical examinations per animal are reported. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
0
21
0
1
Order By: Relevance
“…For example, the survival time was not necessarily longer in sheep with a higher PrP sc score (1452 was culled later than 1424 even though the total PrP sc was two times higher in 1424). Studies on the clinical progression in naturally affected sheep with scrapie suggested that head tremor, ataxia, teeth grinding, loss of body condition and loss of a menace response occurred more frequently with disease progression [29, 40]. There was some indication that sheep with higher PrP sc scores, which had been challenged with milk or brain from the same donor, presented with more severe clinical signs: both brain-challenged VV sheep with a lower PrP sc score (1452 and 1425) were not ataxic and had a menace response unlike the other VV sheep (1424), which was ataxic, lost the menace response and had a considerably higher PrP sc score.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the survival time was not necessarily longer in sheep with a higher PrP sc score (1452 was culled later than 1424 even though the total PrP sc was two times higher in 1424). Studies on the clinical progression in naturally affected sheep with scrapie suggested that head tremor, ataxia, teeth grinding, loss of body condition and loss of a menace response occurred more frequently with disease progression [29, 40]. There was some indication that sheep with higher PrP sc scores, which had been challenged with milk or brain from the same donor, presented with more severe clinical signs: both brain-challenged VV sheep with a lower PrP sc score (1452 and 1425) were not ataxic and had a menace response unlike the other VV sheep (1424), which was ataxic, lost the menace response and had a considerably higher PrP sc score.…”
Section: Discussionmentioning
confidence: 99%
“…2) suggests a higher level of PrP res accumulation in the brainstem, which may indicate that this sheep was in a more advanced clinical stage. As the disease progresses scrapie cases are more likely to react to the scratch test, which was seen in case 05/377, but they also more frequently display head tremor, teeth grinding and an absent menace response [2,22], as seen in case 06/008, and argues against clinical duration being responsible for the observed differences.…”
Section: Discussionmentioning
confidence: 99%
“…Four of the animals exhibited preclinical signs of scrapie, and the diagnoses were made by third eyelid biopsies [26] and confirmed using the rapid test (TeEsE, Bio-Rad) and immunohistochemistry to detect PrP Sc using the 6 H4 monoclonal antibody [27]. This characterization was performed considering the presence of the clinical signs associated with the disease as per previously reported criteria [26].…”
Section: Methodsmentioning
confidence: 99%
“…This characterization was performed considering the presence of the clinical signs associated with the disease as per previously reported criteria [26]. All of the animals belonged to flocks that had been previously characterized as scrapie-affected flocks and were located in different geographical areas.…”
Section: Methodsmentioning
confidence: 99%